The Influence of Media Literacy on Geography Skills Among Geography Education Students - Amelia Zahara; Putra, Exsa; Maryani, Enok; Yani, Ahmad (Universitas Tidar, 2025)
This study investigates the influence of media literacy on the geography skills of students enrolled in the Geography Education Study Program at Universitas Syiah Kuala. In the context of the Fourth Industrial Revolution, media literacy is recognized as a vital competency that supports critical thinking, information evaluation, and digital communication, skills essential for effective geography learning in the 21st century. Using a quantitative descriptive approach, this research involved 169 students selected through simple random sampling from the 2017–2020 cohorts. Media literacy was measured using the Individual Competence Framework, while geography skills were assessed based on indicators from the National Geography Standards (1994). The findings revealed that both media literacy and geography skills among students were generally in the moderate category. Regression analysis showed that media literacy significantly influenced geography skills, with a contribution of 42% (R² = 0.42). These results underscore the importance of integrating media literacy into geography education to enhance spatial inquiry, critical analysis, and digital geocommunication. It is recommended that universities strengthen media literacy training and embed it within geography curricula to foster students' spatial competencies in digital environments.